The Doherty Power Amplifier with pre-amplification stage - Tinjacá-Soler, Jonathan Javier; Cuevas-Carrero, William Alexander; Angarita-Malaver, Edison Ferney; Moreno-Rubio, Jorge Julián (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2015)
This paper shows the general concept of the Doherty power amplifier, highlighting its superiority, in terms of average efficiency, regarding to single-stage power amplifiers. Furthermore, the posibility of including preamplification stages, in both branches of the Doherty power amplifier is presented, with the goal of increasing its gain.